Analisis Kinerja Pemerintah Kelurahan dalam Program Pemberdayaan Kebersihan Kelurahan - Nurmiah, Nurmiah; Kusmanto, Heri; Lubis, Yusniar (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2019)
The purpose of this study was to analyze the performance and constraints of the Kelurahan in the implementation of the Kelurahan cleanliness empowerment program in Kelurahan Tanjungbalai Kota IV. This research was conducted qualitatively by taking informants from the Kelurahan, TP-PKK officials and the community. The results showed that the performance of Tanjungbalai City IV Urban District of North Tanjungbalai District in implementing the cleanliness empowerment program of the Kelurahan was said to be good, because the Kelurahan had formed TP-PKK to create a Clean and Healthy Behavior (PHBS) program with 10 activities and in accordance with the duties and responsibilities in the framework of empowerment Kelurahan. If seen from the accountability dimension of the apparatus that is already quite good with the commitment and seriousness of the Village officials in carrying out their duties and functions in terms of implementing the Tanjungbalai City IV Urban Empowerment program. Judging from the good enough responsibility this can be seen from the ability of the Village in minimizing complaints submitted by the community. And the responsiveness of the Tanjungbalai City IV Kelurahan apparatus is quite good, as seen from the commitment and actions of the Kelurahan officials that are very intense in conducting socialization to the community so that environmental sustainability activities can bring a clean and safe environment,